Vantagens agroeconômica do consórcio de cenoura e caupi-hortaliça sob arranjos espaciais e densidades populacionais - Ribeiro, Giorgio Mendes (2015)
This work was carried out from July 2013 to February 2014 at the Experimental Farm Rafael Fernandes, of the Federal Rural University of the Semi-Arid, Mossoró-RN, in order to determine the agro-economic advantages of carrot and cowpea-vegetable in intercropping under different spatial arrangements and population densities. The experimental design was a randomized complete block with four replications, with the treatments arranged in a 3 x 4 factorial scheme. The first factor was composed of spatial arrangements (2: 2, 3: 3 and 4: 4) and the second factor by the population densities of cowpea-vegetables (100%, 80%, 60% and 40% of the recommended population in sole crop - RPSC). Green manure was made with the incorporation of 51 t ha-1 on a dry basis of roostertree in pre-planting and at 60 days after planting. The characteristics evaluated for carrot were: plant height, total and commercial productivity of roots, fresh mass of shoot, dry mass of roots and classified productivity of roots. For the cowpea-vegetables were evaluated the following characteristics: number of green pods, pod length, yield of green pods, number of green grains per pod, weight of 100-green grains and productivity of green grains. The indices of competition and agro-economic efficiency of intercropping systems assessed were: Aggressivity, competition rate, loss of actual yield, intercropping advantage, land equivalent ratio, productive efficiency index and score of the canonical variable. It was also evaluated the following economic indicators: gross income, net income, rate of return and profit margin. The agro-economic efficiency of carrot and cowpea-vegetable in intercropping system was influenced by the spatial arrangements, with the arrangement 2: 2 standing out from the others. The highest agro-economic efficiency of carrot and cowpea-vegetable in intercropping system was obtained in population density of 90% for cowpea-vegetable in sole crop when the score of the canonical variable had a value of 1.16 and the productive efficiency index of 0.75